2019
DOI: 10.26466/opus.563520
|View full text |Cite
|
Sign up to set email alerts
|

Tarımsal Üretim Gerçekleştiren İşletmelerin Faaliyetlerinin Hedef Maliyet Yöntemine Göre Değerlendirilmesi

Abstract: The factors the production companies should take into account are price, cost and profit. Because pries are determined not by the companies themselves but the markets in competiton within the frame of today's competition approach. Therefore, the companies estimating a ratio pf profit and determinig price according to its costs are obliged to suffer from competition and fail. Instead of the approach above, companies should determine their costs by projecting an amont of profit according to the prices determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Çevik kavramı ilk defa üretim ile birlikte "çevik üretim" olarak Lehigh Üniversitesi Iacocca Enstitüsü tarafından 1992 yılında hazırlanan "21. yy Üretim Stratejisi (21 st Century Manufacturing Enterprise Strategy) isimli raporda kullanılmıştır. Çevik üretim kavramı, "işletmelerin rekabetçi bir çevrede sürekli değişim ve belirsizlik altında başarılı olabilmeleri için izlemeleri gereken yol" (Çetin & Altuğ, 2005) olarak tanımlanabilmektedir. Yazılımda yaygın olarak kullanılan şelale yönteminin etkili ve verimsiz sonuçlarına çözüm olarak geliştirilen çeviklik kavramı, 2001 yılında 17 üyeden oluşan Çevik İttifakı (Agile Alliance) tarafından yayınlanan Çevik Yazılım Geliştirme Manifestosu'nda yer almıştır (Agile Alliance, 2001).…”
Section: çEvik(lik) Kavramının Tanımı Ve Tarihsel Gelişimiunclassified
“…Çevik kavramı ilk defa üretim ile birlikte "çevik üretim" olarak Lehigh Üniversitesi Iacocca Enstitüsü tarafından 1992 yılında hazırlanan "21. yy Üretim Stratejisi (21 st Century Manufacturing Enterprise Strategy) isimli raporda kullanılmıştır. Çevik üretim kavramı, "işletmelerin rekabetçi bir çevrede sürekli değişim ve belirsizlik altında başarılı olabilmeleri için izlemeleri gereken yol" (Çetin & Altuğ, 2005) olarak tanımlanabilmektedir. Yazılımda yaygın olarak kullanılan şelale yönteminin etkili ve verimsiz sonuçlarına çözüm olarak geliştirilen çeviklik kavramı, 2001 yılında 17 üyeden oluşan Çevik İttifakı (Agile Alliance) tarafından yayınlanan Çevik Yazılım Geliştirme Manifestosu'nda yer almıştır (Agile Alliance, 2001).…”
Section: çEvik(lik) Kavramının Tanımı Ve Tarihsel Gelişimiunclassified
“…Numerous studies are dedicated to target costing and analysis (Nicolini et al: 2000;Alagöz et al: 2005;Kalkancı: 2008;Gayret: 2010;Bozdemir and Orhan: 2011;Yereli et al: 2012;Koşan and Geçgin: 2013;Acar and Şenol: 2014;Tandoğan and Şahin: 2014;Okutmuş and Ergül: 2015;Terzi: 2017;Karahan: 2018;Karaosman: 2019;Güveş: 2019;Çetin and Bahşi: 2019;Görücü: 2019). These relevant studies and more have highlighted that target costing can be applied in any sector and can be integrated into various research endeavors.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings indicated that the target costing approach empowers businesses to effectively manage their costs in line with market sales prices, allowing them to allocate their investment funds strategically to productive areas. Çetin and Bahşi (2019) examined the feasibility and advantages of implementing target costing in agricultural production activities. The research findings revealed that for successful implementation of target costing, the entire enterprise must be involved in this process, and it should be carried out before the actual production phase.…”
Section: Introductionmentioning
confidence: 99%